GRACEFUL LABEING AND RHO TOPI LABELING ON THE 8-BINTANG GRAPH WITH C3 FOR N ODD - Amri, Zulfi; Harahap, Tua Halomoan; Irvan, Irvan (UIN Sumatera Utara, 2018)
This paper we propose graceful labeling and labeling on a graph then referred to as 8-Bintang graph, the basic idea of formulation graceful labeling and labeling on an alfabet bintang graphs wih the question a stars graph . Then we constructing graceful labeling and labeling on the 8-Bintang graph with circle graph for odd. The results obtained are illustrated in the theorem that the 8-Bintang graph with for odd has the following graceful labeling with the proof.